Identification of Glycosylated Tick Proteins Containing Immunogenic Epitopes - Dvorníková, Zuzana (Jihočeská univerzita, 2023)
Glycosylation is one of the most common post-translational modifications of proteins. The saccharide parts bound to the proteins then plays a role in triggering immune responses. Ticks are blood-sucking parasites that transfer different pathogens into the human body, causing very serious illnesses. However, transmission of the pathogens via ticks still hasn't been fully described in terms of its process. The aim of this thesis was to identify and purify proteins carrying potentially immunogenic alpha1,3-core fucose, sialic acid, and galactose-alpha-1,3 galactose epitopes from IRE/CTVM20, ISE18, and OME/CTVM22 tick cell lines using biochemical methods and subsequent mass spectrometry analysis. Furthermore, visualisation of individual epitopes in every cell line using fluorescence microscopy was done.
Identification of Glycosylated Tick Proteins Containing Immunogenic Epitopes